SIM PSR: A Web-Based Monitoring Platform for Cooperative-Level Smallholder Palm Oil Replanting Program Management - Syarifatu Assolehah; Ritna Wahyuni; Raden Aris Sugianto (Academic Bright Collaboration, 2026)
Purpose – The Smallholder Palm Oil Replanting Program (PSR) seeks to improve the productivity of smallholder plantations by replacing aging oil palm trees with certified superior seedlings. However, monitoring at the cooperative level is often hindered by manual record-keeping and fragmented reporting, reducing the efficiency of supervising program implementation. This study aims to develop and evaluate a web-based monitoring information system for the PSR program at Koperasi Tani Makmur Berjaya, Air Hitam Village, North Labuhanbatu Regency. Methods – The system was developed using the Waterfall methodology with UML-based system modeling and implemented using PHP and MySQL. It supports three user roles administrator, field officer, and participant with permissions tailored to operational responsibilities. Functional performance was evaluated through developer-conducted Black Box Testing across 25 functional test scenarios involving administrator, field officer, and participant roles. Findings – Functional testing demonstrated that the proposed system supports the management of participant information, land data, documents, stage-based monitoring records, and PDF report generation under controlled testing conditions. It supports monitoring for 116 participants across approximately 480 hectares in five villages. Testing confirmed that all functions operated as intended without identified functional failures. Research Implications – The proposed system provides a centralized digital platform for cooperative-level PSR monitoring. However, the findings are limited to a single cooperative implementation and developer-conducted functional testing, without independent usability evaluation, independent or advanced security assessment, or long-term operational validation beyond the basic internal security checks conducted in this study. Originality – This research presents a web-based monitoring system specifically designed for cooperative-level PSR management in Indonesia, integrating role-based access control, stage-oriented progress monitoring, and automated report generation within a unified platform.